Agricultural value chain finance in Myanmar - Basu, Siddhartha; Oo, Khin Pwint; Aung, Lwin Lwin; Middleton, Mark; Moyes, Tom; Toth, Russell; de Brauw, Alan (Australian Centre for International Agricultural Research, 2020)
Smallholder farmers in developing countries face substantial constraints that limit their ability to reach their production potential. Two constraints—risk exposure and limited access to liquidity—pose particular challenges. Smallholders face a wide variety of risks that constrain the choices they can make and their willingness to make investments. Limited availability of affordable credit, borrowing, and saving products poorly aligned with the needs of the agricultural sector as well as prohibitive borrowing eligibility requirements all impede farmers’ access to the liquidity necessary for investing in new, more profitable crops or technologies (International Finance Corporation, 2014). Observers have noted that a large share of long-term credit needs is not being met in Southeast Asia (Shakhovskoy and Wendle, 2013). The location of the region’s agricultural sector near some of the world’s largest consumer markets is creating new opportunities throughout Southeast Asia.